Implementasi Cloudflare Zero Trust Dalam Mendeteksi Aktivitas Cryptojcking Pada Jaringan Komputer - Sandi Adhar; Usep Saprudin (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
With the increasing popularity of cryptocurrency (cryptocurrency) causing high crypto mining activity, crypto mining requires large resources so that many cybercriminals carry out illegal activities by stealing access to other people's computers to be used to mine cryptocurrencies (cryptojacking), this can interfere with the performance of a computer if the computer is used illegally without the knowledge of the computer owner, apart from that crypto mining also runs by utilizing the internet network, CPU usage and the power source from the victim's computer, for this reason this research will implement software as service (Saas) services from Cloudflare zero trust that can detect and anticipate cryptojacking activities on the internet network in order to anticipate attacks, Cloudflare zero trust will be installed on the network using the MikroTik routerboard intermediary, besides that the author will conduct an attack trial (penetrator si testing) by carrying out crypto mining activities on computers in a network and analyzing whether Cloudflare Zero Trust is able to detect and anticipate these attacks.